Queen succession conflict in the paper wasp Polistes dominula is mitigated by age-based convention. (20th May 2020) - Taylor, Benjamin A; Cini, Alessandro; Cervo, Rita; Reuter, Max; Sumner, Seirian
Abstract: Reproduction in cooperative animal groups is often dominated by one or a few individuals, with the remaining group members relegated to nonreproductive helping roles. This reproductive skew can evolve if helpers receive fitness benefits such as potential future inheritance of the breeding position, but the mechanisms by which inheritance is determined are not well resolved. Polistes paper wasps form highly reproductively skewed groups and inheritance of the breeding position is likely to play a key role in the maintenance of this social structure, making them excellent models for the processes by which simple societies are maintained. Reproductive succession is thought to be determined via an age-based convention in some Polistes species, but there is also evidence for contest-based succession systems in which the replacement queen uses physical aggression to overpower and thereby subordinate her nestmates. Here, we provide evidence that queen succession in colonies of the European paper wasp Polistes dominula is determined via convention rather than contest, with little disruption to the colony's social functioning. We use queen removal experiments and fine-scale behavioral analyses to confirm that age is a strong predictor of succession, and that behavioral responses to queen removal are restricted to the oldest individuals rather than being experienced equally across the group. We provide the most comprehensive and detailed experimental analysis on the dynamics of breeder succession in a cooperatively breeding invertebrate to date, thereby shedding light on the mechanisms by which animal societies are able to maintain cohesion in the face of within-group conflict. Abstract : When societies lose a leader, the result can be an orderly succession process or all-out fighting. Following the loss of their queen, colonies of European paper wasps promote one or more older workers as replacements, even though older wasps are not larger or more reproductively developed. This succession mechanism allows the replacement of the queen without costly in-fighting, minimizing the costs of queen loss.